PENGGUNAAN KALIMAT DALAM MENCERITAKAN KEMBALI KISAH TOKOH ALKITAB DI SEKOLAH MINGGU GEREJA UTUSAN PANTEKOSTA JEMAAT MADIUN - Rustiati, Rustiati; Marpaung, Marpaung (Educatio Vitae, 2015)
This research is to know kinds of setences whrch are used by teachers at  Sunday School in reletelling about bible’s characters at Sunday School of GUP “HARVEST” Madiun based on their meaning and their quantity of clauses. The date is setences whrch are spoken then transcripted into 7 kinds of writing at Sunday School. They are namely: (1) they song of herdsmen welcoming the born of Jesus Christ, (2) King Ahab, (3) Micah prophet, (4) Jesus heals his mother in low, (5) sunem’s women, (6) Marta and Maria, and (7) Maria, Jesus mother. The result of analysis. 1. Kind of setences whrch is used based on their meanings, there are 185 setences, then brouped based on the kind of setences seen from the meaning, namely report sentences which are found 121 times. There are 12 imperative setences are found. There are question 25 setences are found, then groupet into 2 kinds of question, namely there are 18 setences in common question and 7 setences rethorical question. There are 27 attentive setences are found.2. Kind of setences based on the number of clauses found 57 complete setences and 40 compound setences, then groupet based on the relation among clauses found 27 equal compaund sentences do note exist. In conclusion, report setences of declarative sentences are the most in use because the research’s characteristic is to report a story at event and complete sentences is more in  uis than compound sentences because the listeners of the research are children. Keywords: Sentence, Bible, Church